Sifat Kimia Ultisol di Bawah Tegakan Berbagai Umur Tanaman Kelapa Sawit (Elaeis guineensis jacq.) - Dedi Hayadi; Wawan '; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research is to determine the chemical properties of Ultisol under the oil palm stands of different ages between on the oil palm circle, life path and die path with different depths. This research was conducted by survey method. The sample collection is done by purposive sampling. The results of the research showed that the increasing age of the oil palm plantations has increased Ultisol chemical properties. The chemical properties of Ultisol under the stand of oil palm age of 18 years is the highest compared to the age of 8 and 15 years. pH and higher organic-C in the die path than in the circle , and the disc is higher than in life path. Total-N, available P, exchangeable bases, CEC, and base saturation is higher in the oil palm circle than in die path, and some chemical properties of Ultisol in die path is higher than in life path. In general, the chemical properties of Ultisol at a depth of 0-20 cm have a higher value than the depth of 20-40 cm. Keywords: Chemical Properties of The Soil, Ultisol, Oil palm